Effects of astragaloside IV on the pharmacokinetics of omeprazole in rats - Wei Liu (Taylor & Francis Group, 2019)
Context: Omeprazole and astragaloside IV (AS-IV) are widely used for the treatment of gastric ulcers in China clinics. Objective: This study investigates the effects of AS-IV on the pharmacokinetics of omeprazole in rats. Materials and methods: The pharmacokinetics of orally administered omeprazole (2 mg/kg), with or without AS-IV (100 mg/kg/day for 7 days) pretreatment, were investigated in male Sprague-Dawley rats (two groups of six animals each) using LC–MS/MS. A Caco-2 cell transwell model and rat liver microsome incubation systems were also used to support the in vivo pharmacokinetic data and investigate its potential mechanism. Results: The results indicated that co-administration of AS-IV could decrease the systemic exposure of omeprazole significantly (p < 0.05), including AUC0–t (717.20 ± 177.63 vs. 1166.25 ± 186.65 ng h/mL) and Cmax (272.35 ± 25.81 vs. 366.34 ± 32.57 ng/mL). The t1/2 of omeprazole also decreased significantly (1.78 ± 0.15 vs. 2.23 ± 0.27 h, p < 0.05). The efflux ratio of omeprazole across the Caco-2 cell transwell model increased significantly from 1.73 to 2.67 (p < 0.05), and the metabolic stability of omeprazole was decreased from 42.6 ± 7.8 to 26.2 ± 5.1 min with the pretreatment of AS-IV (p < 0.05). Discussion and conclusions: AS-IV could decrease the systemic exposure of omeprazole in rats when AS-IV and omeprazole were co-administered, and it might exert these effects through decreasing the absorption of omeprazole by inducing P-gp, or through accelerating the metabolism of omeprazole in rat liver by inducing the activity of CYP3A4.